BENARKAH IKLAN ONLINE EFEKTIF UNTUK DIGUNAKAN DALAM PROMOSI PERUSAHAAN - Santoso, Erica Delia; Larasati, Novia (LP2M Institut Teknologi dan Bisnis Asia Malang, 2019)
At this time technology is growing well, so that the existing technology becomes sophisticated. Sophisticated technology can be utilized to conduct marketing activities such as promotional activities like promotional products via the internet (online advertising). The development of online advertising in Indonesia is currently growing rapidly, so when opening the internet, online advertising is always appear. Too much online ads that appear not necessarily make the internet media as the right media. Online advertising can be said to be ineffective because based on research states that people avoid advertising because it interferes with the main purpose when accessing the internet. However, on the other hand online advertising can be said to be effective because of its wide range, it can determine segmentation, and need low budget. Therefore, this topic needs to be examined more deeply to see if online advertising is really effective or not.